Ireland and the Magdalene Laundries: a campaign for justice - O'Donnell, Katherine; McGettrick, Claire; Smith, James M.; O'Rourke, Maeve; Steed, Mari (I.B. Tauris, 2021)
Introduction -- Chapter 1: Ireland's Magdalenes: Historical, Theological and Political Contexts -- Chapter 2: The Justice for Magdalenes Campaign -- Chapter 3: The Deep State Fights Back and a Movement Rises -- Chapter 4: Of Men and Money: Hiding the Galway Archive -- Chapter 5: Bringing up the Dead: the Land Deals and Burials at High Park -- Appendix -- Bibliography -- Index.